2019
DOI: 10.1111/bjet.12784
|View full text |Cite
|
Sign up to set email alerts
|

Integrating games as a means to develop e‐learning: Insights from a psychological perspective

Abstract: Although the Education sector has pioneered the use of technology, the pace of technological change has outstripped the slower processes of theoretical development and critical reflection, so the field is highly fragmented and lacks a comprehensive evidence base to support future development. In this paper, we consider how the insights offered by games and a psychological perspective can address the current challenges. Both games and e-learning specialists are facing similar challenges and would therefore bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…However, intrinsic motivation refers to doing something because it is appealing or pleasant, and it is related to three aspects: autonomy, relationship, and competence [8,33,89,101]. Some factors encourage motivation: competition, challenge, imagination, collaboration, goals, cooperation, reward, and recognition, many of which are present in games [12,28,39,87,91,97,100].…”
Section: Behavioral Attitudes Associated With Gamificationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, intrinsic motivation refers to doing something because it is appealing or pleasant, and it is related to three aspects: autonomy, relationship, and competence [8,33,89,101]. Some factors encourage motivation: competition, challenge, imagination, collaboration, goals, cooperation, reward, and recognition, many of which are present in games [12,28,39,87,91,97,100].…”
Section: Behavioral Attitudes Associated With Gamificationmentioning
confidence: 99%
“…In addition to motivation, educational games improve interest and concentration, improving students' learning [94]. [55]; Terras and Boyle, 2019 [12]; Romero-Rodríguez et al, 2019 [11]; Gauthier and Jenkinson, 2018 [71]; Kyewski and Krämer, 2018 [8]; Pérez-Manzano and Almela-Baeza, 2018 [72]; Olszewski et al, 2018 [73]; Jackson et al, 2018 [74]; Ge, 2018 [75] [88]; Fitó-Bertran, Hernández-Lara, and López, 2015 [114]; Ibáñez, Di-Serio, and Delgado-Kloos, 2014 [106]; Zafar, Safdar, and Zafar, 2014 [115]; Martín-SanJosé et al, 2014 [28]; Jackson and McNamara, 2013 [92]; Sancho, Torrente, and Fernández-Manjón, 2012 [95]; Kanthan and Senger, 2011 [96]; Moreno-Ger et al, 2010 [109]; Regueras et al, 2009 [98] Engagement is another behavioral attitude identified as a valuable indicator of academic performance and positively correlates with student learning outcomes [103,106], as seen in 26 articles. Engagement happens when someone's attention is completely focused on a specific activity.…”
Section: Behavioral Attitudes Associated With Gamificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplanted to the game-based learning context, flow theory has been widely applied for understanding how learning through games approximates flow and peak experience that allow learners to be absorbed in the game-based learning experience and arrive at enhanced learning outcomes thereafter (Kasurinen and Knutas, 2018;Koivisto and Hamari, 2019;Reiners and Wood, 2015;Sweetser and Wyeth, 2005;Terras and Boyle, 2019). Competitive games, in both serious games and game-based learning contexts, have been suggested to be associated with variations in flow experience pertaining from game experience, including challenge (Cairns, 2016), feedback on learning (Chapman and Rich, 2018), as well as autonomy and social relatedness (Sailer et al, 2017).…”
Section: Introduction Backgroundmentioning
confidence: 99%